2017
DOI: 10.1007/s10029-017-1706-8
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of giant paraesophageal hernia: pro laparoscopic approach

Abstract: The laparoscopic treatment of primary and secondary GPEH is safe and feasible in elective and emergency settings, especially in high-volume centers. The procedure is still challenging. The main steps are well defined. However, there is still room for improvement to lower the recurrence rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
15

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 59 publications
1
27
0
15
Order By: Relevance
“…As surgeons have improved laparoscopic operation techniques, results have improved over time and experience. The recurrence rates of laparoscopic repair of GPEH in retrospective series ranged from 12 to 21% [11,34]. However, in a recent prospective series the rate was as high as 32.7% at 1 year.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…As surgeons have improved laparoscopic operation techniques, results have improved over time and experience. The recurrence rates of laparoscopic repair of GPEH in retrospective series ranged from 12 to 21% [11,34]. However, in a recent prospective series the rate was as high as 32.7% at 1 year.…”
Section: Discussionmentioning
confidence: 95%
“…The long-term outcomes and durability of laparoscopic repair are debated [10][11][12]. Complex laparoscopic repair of GPEH has been reported to be safe and successful [13][14][15] and the postoperative length of stay is shorter and postoperative pain is less severe than after open surgery [11,16]. On the other hand, radiological evidence of recurrence after laparoscopic surgery is often higher than after open repair [17].…”
Section: Introductionmentioning
confidence: 99%
“…Before performing fundoplication surgery it is also essential to verify the integrity of the peristaltis of the esophagus, which can be done using high resolution manometry (HRM) as it provides real time pressure recording [3,5]. However, placement of the manometry catheter can be rather difficult; Dallemagne et al have reported that the method is completed in less than 50% of cases [17].…”
Section: Diagnosis Of Esophageal Hiatal Herniamentioning
confidence: 99%
“…Usually, it is discovered incidentally while performing CT scan for a different indication [5]. Dallemagne et al recommend CT scan in order to rule out complications like perforation, pneumoperitoneum or pneumomediastinum [17]. In case of paraesophageal hernia, it is a helpful method in the assessment of gastric volvulus [5].…”
Section: Diagnosis Of Esophageal Hiatal Herniamentioning
confidence: 99%
See 1 more Smart Citation